Nilai–Nilai Pendidikan Akhlak Dan Budi Pekerti Dalam Tradisi Pembacaan Shalawat Kitab Al - Barzanji: (Kajian Deskriptif di Dusun Nglegok, Desa Kranding, Kecamatan Mojo, Kediri) - Erika Diyah Ayu Utari; Bagus Wahyu Setyawan; Amelia Nailul Muna; Nurul Hidayatut Thoyibah; Bilqis Malika Auliya (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This study aims to describe the implementation of the Al-Barzanji recitation tradition and to identify the moral education values embedded within it in Nglegok Hamlet, Kranding Village, Mojo District, Kediri Regency. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that the Al-Barzanji recitation tradition is still regularly practiced in various religious and social activities within the community. This tradition functions not only as a religious ritual but also as a medium for moral education. The moral values identified include devotion to Allah SWT, respect for Prophet Muhammad SAW, obedience to parents, responsibility toward children and family, and positive social behavior. These values are internalized through the recitation and appreciation of the exemplary life stories of Prophet Muhammad SAW contained in the Al-Barzanji text. Furthermore, the tradition contributes to strengthening social solidarity, preserving religious identity, and maintaining local Islamic cultural heritage amid social change. Keywords : Moral Education Values; Character Building, Al-Barzanji Book; Tradition of Reciting Shalawat; Living Islam.